Body-Posture Recognition by Undergraduate Students Majoring in Physical Education and Other Disciplines - Tao, Weidong; Du, Bixuan; Li, Bing; He, Weiqi; Sun, Hong-Jin (Frontiers in Psychology, 2020)
Using whole-body and piecemeal-body postures as stimuli, we performed two experiments to investigate whether body-posture recognition differed between two groups of participants: undergraduates majoring in physical education (PE) and those in other subjects (non-PE), respectively. These two groups differed significantly in the frequency and intensity of exercise per day and/or accumulated exercise time. Our results showed that, in Experiment 1, for whole-body posture recognition, both the PE and non-PE groups showed a robust body-inversion effect in terms of both error rate and reaction time (RT), but the magnitude of the body-inversion effect in the RT measure was greater in the PE than the non-PE group. In Experiment 2, for piecemeal-body postures, both group showed the inversion effect in terms of both error rate and RT measures and the PE group made fewer overall errors than did the non-PE group. These cumulative results suggest that a superiority effect exists for PE participants compared to non-PE participants. Our results are generally consistent with the expertise hypothesis.